Analysis of Various Performance Factors Determining Rice Prices in East Java Province - Hatta, Mochammad; Tjahjani, Ida Kusnawati (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: This research aims to analyze various performance factors determining rice prices in East Java Province Design/methodology/approach: Quantitative data analysis in the form of production performance analysis, marketing analysis with a focus on performance analysis of each supply chain, development analysis and price formation analysis. Meanwhile, qualitative data analysis related to rice milling performance and yield as well as supporting descriptions of the various analyzes that have been carried out. Findings: The research results show that the price of rice is determined by various performances factors, namely production performance, marketing with a focus on performance of each supply chain, development and price formation, rice milling performance and yield as well as supporting descriptions Research limitations/implications: This study is limited to areas that have the same geographical conditions. Practical implications: This research is limited to areas that have similar geographical conditions. Originality/value: This research is original. Paper type: Case Study